Effects of Ramadan fasting on perceived exercise intensity during high-intensity interval training in elite youth soccer players - Aziz, A. R.; Chia, M.; Singh, R.; Wahid, M. F. (International Journal of Sports Science and Coaching, 2011)
In the Islamic holy month of Ramadan, able-bodied Muslims consume food or fluid during the permissible period from after dusk and before dawn. Muslim athletes continue to train during Ramadan. In Original Research, Abdul Rashid Aziz, Michael Chia, Rabindarjeet Singh and Mohamed Faizul Wahid report a field investigation of the impact of Ramadan fasting on the dependent variables of perceived exercise intensity and actual maximal aerobic performance during high-intensity training sessions by youth soccer players (eighteen members of the National Under-18 squad). During the Ramadan month, both a fasting group and a control group underwent six specific conditioning sessions consisting of high-intensity aerobic and anaerobic interval training in addition to their normal soccer training. There were no significant effects of fasting on the dependent variables.